Answer:
Alisha's approach is simpler and less complicated
Explanation:
Given:
(m^2*n^-3) / (m^6*n^-1)
Tyrone's approach.
(m^2*n^-3) / (m^6*n^-1)
(m^2*n^-3)^3 / (m^6*n^-1)^3
You can find the cube root of both the numerator and denominator in order to eliminate the third power
3√((m^2*n^-3)^3 / 3√(m^6*n^-1)^3
This will take us back to the original expression
(m^2*n^-3) / (m^6*n^-1)
= m^(2-6)*n^(-3+1)
= m^-4*n^-2
= 1/(m^4*n^2)
Alisha's approach.
(m^2*n^-3)/(m^6*n^-1)
= m^(2-6)*n^(-3+1)
= m^-4*n^-2
= 1/(m^4*n^2)
The approach of both of them are correct, however, Tyrone's approach will make the expression more complicated but they would still arrive at the same answer. 1/(m^4*n^2)